Christmas fairs in Danish churches abroad: a resource mobilisation perspective. Issue 3 (3rd July 2018) - Warburg, Margit
ABSTRACT: An important source of income for Danish churches abroad is the profit from the traditional Christmas fairs. Arranging a successful Christmas fair requires that the church engages in a resource mobilisation effort to get donations of goods and free services for the fair and to raise voluntary labour among the local expatriate Danes. This requires a concern for both Gemeinschaft and Gesellschaft . Data on economy and number of person-hours spent on Christmas fairs at five Danish churches abroad showed that the profitability of the fairs could be questioned in some cases. During field studies at three of these Christmas fairs, I investigated many volunteers' motives for spending their time and efforts on the Christmas fair. I also tested their willingness-to-accept (hypothetically) to substitute the Christmas fair with an annual lump sum. The answers showed that the Christmas fairs are highly valued for their strengthening of Gemeinschaft in the expatriate milieu.